Chemoradiotherapy Versus Chemotherapy Alone for Advanced Esophageal Squamous Cell Carcinoma: The Role of Definitive Radiotherapy for Primary Tumor in the Metastatic Setting - Li, Li-Qing; Fu, Qing-Guo; Zhao, Wei-Dong; Wang, Yu-Dan; Meng, Wan-Wan; Su, Ting-Shi (Frontiers in Oncology, 2022)
Introduction The role of definitive radiotherapy in advanced esophageal squamous cell carcinoma (ESCC), especially in the metastatic setting, remains unclear. Therefore, we aimed to investigate the efficacy of chemoradiotherapy (CRT) versus chemotherapy (CT) alone in these selected patients. Methods We retrospectively evaluated 194 newly diagnosed advanced ESCC who underwent definitive CRT or CT alone, including 97 patients with locally advanced and 97 patients with distant metastatic disease. Cumulative overall survival (OS) and progression-free survival (PFS) were evaluated with a log-rank test. Propensity score matching was used to simulate random allocation. In addition, we performed subgroup analysis in the locally advanced and metastatic disease. Results After matching, 63 well-paired patients were selected. The adjusted median OS (12.5 vs. 7.6 months, p = 0.002) and PFS (9.0 vs. 4.8 months, p = 0.0025) in the CRT group were superior to that in the CT-alone group. Further subgroup analysis revealed that CRT conferred survival benefits to both locally advanced and metastatic cohorts. For patients with distant metastasis, median OS (12.9 vs. 9.3 months, p = 0.029) and PFS (9.9 vs. 4.0 months, p =0.0032) in the CRT group were superior to that in the CT-alone group. In a multivariate Cox regression analysis of the entire cohort, additional definitive radiotherapy was independently associated with better OS (p = 0.041) and PFS (p = 0.007). Conclusions In both locally advanced and metastatic ESCC, additional definitive-dose radiotherapy was associated with improved clinical outcomes. Therefore, more consideration should be given to its application in the metastatic setting.